STRATEGI KETAHANAN KELUARGA SAKINAH PADA MAHASISWA YANG TELAH MENIKAH: Studi Fenomenologi pada Mahasiswa Berkeluarga STDI Imam Syafi’i Jember - Muhammad Yusup Rustam; Ruston Kumaini; Ghufran Jauhar (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
ABSTRACT This research examines in depth how the strategies implemented by married couples who are students in building a family that is sakinah, mawaddah, and rahmah. Researchers found phenomena that are not a few students who are married while studying at Islamic Studies College of Imam Shafi’i Jember. This research uses qualitative methods with a phenomenological study approach. Individual exploration in phenomenology is examined and explored in depth through in-depth interviews about individual experiences in the context of their daily lives to obtain data for analysis. The results of data analysis from this study are that there are two major points that help married students succeed in carrying out their lecture activities while taking care of the family, namely: (1) The availability of educational assistance that meets the needs of tuition fees. (2) The wife's very dominant role in taking care of the house, children and husband's needs. Furthermore, the situation of husbands and wives who try to fulfill their rights and obligations to their spouses where the husband, who is a student, still tries to fulfill his wife's livelihood both in the form of physical and mental sustenance and the wife also tries to carry out her duties properly in taking care of the household, managing children and fulfilling the husband's needs is a manifestation of the concept of sakinah in which there is a sense of love and affection (Mawaddah wa Rahmah). Keywords: strategies, married students, sakinah family